Optimization of rooster semen preservation: a comparative study of extender types and antioxidant supplementation strategies during cold storage - Ruthaiporn Ratchamak; Supakorn Authaida; Thirawat Koedkanmark; Himalai Saiyamanon; Wuttigrai Boonkum; Vibuntita Chankitisakul (Poultry Science)
This study evaluated the effect of semen extenders and antioxidant supplementation strategies on the quality and fertility of Thai native rooster semen during cold storage. In Experiment 1, four extenders (EK, IGGKPh, NaCl, and NCAB) were evaluated for their ability to preserve sperm motility, viability, lipid peroxidation (MDA), and oxidative stress (reactive oxygen species; ROS) over 24 h at 5°C. EK and IGGKPh extenders yielded superior motility (68.72% and 70.27%) and viability (91.96% and 91.97%) while minimizing MDA (0.93 and 1.12 µmol) and ROS (14.44% and 14.04%) compared to NaCl (motility: 53.14%, viability: 82.09±3.15, MDA: 1.59 µmol; P < 0.01). Experiment 2 examined the effects of dietary selenium (0.6 ppm), extender-based glutathione (GSH) supplementation (2mM), and their combination across all extenders. Antioxidant treatments, particularly GSH and its combination with selenium, improved motility, viability, and oxidative stability (P < 0.05). At 24 h, GSH-enriched groups using EK and IGGKPh exhibited enhanced motility (67.90% and 71.49%) compared to the controls (57.97% and 55.09%). In the NaCl group, GSH and combined treatments significantly improved motility at 12 h (50.83% and 50.01%, respectively) compared to the control (40.80%; P < 0.01). Selenium also increased sperm concentration (4.24 ± 0.55 × 10⁹ vs. 2.46 ± 0.22 × 10⁹ spz/mL; P < 0.01). Experiment 3 fertility outcomes using EK extender and the same antioxidant treatments from Experiment 2. Fertility rates were significantly higher in the GSH (70.38%) and combined (69.16%) groups than in the control (54.26%; P < 0.01), while hatchability remained unaffected (P > 0.05).In summary, the composition of the extender and antioxidant strategy has a significant influence on semen quality and fertility. The EK and IGGKPh extenders, especially when supplemented with GSH, offered superior protection, and combining dietary selenium with GSH yielded synergistic benefits for semen preservation and reproductive success.